PEMANFAATAN TANAMAN OBAT BERBASIS KEARIFAN LOKAL DALAM PEMBELAJARAN BIOLOGI KONTEKSTUAL DI SMA NEGERI 9 DENPASAR - A.A. Istri Mirah Dharmadewi; Kadek Novy Susana; Desak Gede Trisna; Herlina Lium (Program Studi Pendidikan Biologi Universitas PGRI Mahadewa Indonesia, 2024)
Local wisdom is a learning resource rich in ecological, social, and cultural values ​​that can be utilized in education, especially biology learning. In Bali, the use of medicinal plants by the community is not only for traditional medicine, but also part of the cultural heritage that reflects the harmonious relationship between humans and nature. This study aims to explore and integrate the potential of local medicinal plants as contextual learning resources in biology subjects at SMA Negeri 9 Denpasar. The method used is an exploratory qualitative study through observations of the school environment, interviews with community leaders and biology teachers, and documentation of local ethnobotany references. The results of the exploration showed that there are at least twelve species of medicinal plants commonly used by the local community, including temulawak (Curcuma xanthorrhiza), cat's whiskers (Orthosiphon aristatus), and pule pandak (Rauvolfia serpentina). These three plants have interesting morphological characteristics to study as well as pharmacological properties that are relevant to public health issues. The integration of these plants in biology learning is carried out through a contextual approach, such as herbarium creation projects, identification of plant structures, and creation of educational videos based on field studies. This activity increases student engagement in the learning process and strengthens the relationship between biological concepts and local realities around them. This finding emphasizes the importance of integrating local knowledge into the school curriculum as a strategy to enrich open materials, increase learning motivation, and foster awareness of conservation and preservation of local culture. This study recommends the development of systematic local wisdom-based teaching materials as a concrete step in supporting Independent Learning and preserving local identity through education.